Staphylococcus aureus-derived extracellular vesicles induce monocyte recruitment by activating human dermal microvascular endothelial cells in vitro - Kim, Jihye; Bin, Bum Ho; Choi, Eun Jeong; Lee, Hyun Gee; Lee, Tae Ryong; Cho, Eun Gyung (Clinical and Experimental Allergy, 2019)
Background: Atopic dermatitis (AD) represents the most common inflammatory skin disorder in children showing massive infiltration of immune cells. The colonization of AD-afflicted skin by Staphylococcus aureus and S. aureus-derived extracellular vesicles (SEVs) has been associated with AD pathogenesis; however, the molecular mechanism underlying SEV-mediated inflammatory responses remains unclear. Objective: We investigated how SEVs can mediate inflammatory responses in AD pathogenesis by examining the effect of SEVs on human dermal microvascular endothelia cells (HDMECs). Methods: HDMECs were treated with SEVs, and the expression of cell adhesion molecules or cytokines was assessed using RT-qPCR, Western blot or cytokine array analyses. The receptor for SEVs and related signalling molecules in HDMECs were addressed and verified via gene knockdown or inhibitor experiments. The recruitment assay of human THP-1 monocytic cells on HDMECs was performed after SEV treatment in the presence or absence of the verified receptor or signalling molecule. Results: SEVs, but not other gram-positive bacteria-derived extracellular vesicles, directly activated HDMECs by increasing the expression of cell adhesion molecules (E-selectin, VCAM1 and ICAM1) and that of IL-6, the inflammatory cytokine; consequently, they enhanced the recruitment of THP-1 monocytic cells to HDMECs. The SEV-induced HDMEC activation was dependent on Toll-like receptor 4 and the NF-κB signalling pathway, which was rapidly activated within 1 hour post-treatment and followed by an upregulation of cell adhesion molecules and IL-6 at later time-points. Moreover, SEV-mediated HDMEC responses were more rapid and intense than those induced by the same protein concentrations of S. aureus extracts. Conclusions & Clinical Relevance: SEVs as proinflammatory factors could mediate immune cell infiltration in AD by efficiently inducing endothelial cell activation and monocyte recruitment, which may provide insights into alleviating the S. aureus-mediated onset or progression of AD and its phenotypes.
Keywords: Cell Line; Dermatitis, Atopic; Dermis; Endothelial Cells; Extracellular Vesicles; Humans; Microvessels; Monocytes; Staphylococcus aureus